Liquid organic fertilizer concentration of pineapple peel on the growth and production of black potato, Plectranthus rotundifolius (poir.) Spreng - Nurlaila Nurlaila; Firdaus Sulaiman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
The research aimed to determine the effect of applying liquid organic fertilizer from pineapple peel on the growth of black potato, Plectranthus rotudifolius (poir) Spreng. In this research the method used was Randomized Block Design (RBD) method with six treatment levels, each treatment repeated four times across four blocks, resulting in 24 experimental units. In this study, six treatments were applied, consisting of various concentrations of liquid organic fertilizer from pineapple peel P0 = no treatment, P1= 10%, P2= 15%, P3= 20%, P4= 25% and P5= 30. The research used manure and NPK fertilizer as basic fertilizer in soil planting media. The results showed that the application of pineapple peel had a significant effect on the growth parameters of black potatoes, especially on root fresh weight, shoot fresh weight and tuber volume, treatment P4 (25%) produced the highest shoot fresh weight, average 535.75 g, while P2 the lowest average was 332.25 g, the highest fresh root weight was 18.25 g, while the lowest P1 was 10.75 g and tuber volume had a significant effect on treatment P2 (15%) producing the highest volume namely 4.89 g, while the lowest was 4.10 g. The application of 15% pineapple peel liquid organic fertilizer significantly increased crown fresh weight, root fresh weight, and tuber volume of black potato, while having no significant effect on other growth parameters.